CpG hypermethylation contributes to decreased expression of PTEN during acquired resistance to gefitinib in human lung cancer cell lines. Issue 3 (March 2015) - Maeda, Masashi; Murakami, Yuichi; Watari, Kosuke; Kuwano, Michihiko; Izumi, Hiroto; Ono, Mayumi
Highlights PTEN overexpression restored the sensitivity to EGFR-TKI in resistant cells. EGR-1 did not have a critical role in decreased expression of PTEN in gefitinib-resistant cells. Demethylation of the PTEN promoter by 5AZA-CdR upregulated PTEN expression.